2015
DOI: 10.1007/s00382-015-2598-x
|View full text |Cite
|
Sign up to set email alerts
|

Inherent characteristics of sawtooth cycles can explain different glacial periodicities

Abstract: change, while the forcing periodicity remains fixed, due to either random variations or different frequency components of the orbital forcing. Two key relationships stand out as predictions to be tested against observations: (1) the amplitude and the periodicity of the cycles are approximately linearly proportional to each other, a relationship that is also found in the δ 18 O temperature proxy. (2) The magnitude of the spikes increases with increasing periodicity and amplitude of the sawtooth. This prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(50 citation statements)
references
References 66 publications
0
50
0
Order By: Relevance
“…The multibox model was modified from an earlier version used in Omta et al (2013Omta et al ( , 2016. The initial tracer concentrations are listed in Table A1, along with their respective values at the end of the spin-up.…”
Section: Appendix A: Multibox Setupmentioning
confidence: 99%
“…The multibox model was modified from an earlier version used in Omta et al (2013Omta et al ( , 2016. The initial tracer concentrations are listed in Table A1, along with their respective values at the end of the spin-up.…”
Section: Appendix A: Multibox Setupmentioning
confidence: 99%
“…First, a detailed discussion of the timing of CO 2 and the benthic isotopic record leaves open the possibility that at the timescale of the glacial-interglacial cycle the CO 2 simply acts as a feedback on ice volume (Ruddiman, 2006), even if it is also observed that the dynamics of the deglaciation are complex and that CO 2 changes can go through fairly abrupt dynamics (Ganopolski and Roche, 2009). On the other hand, other potential elements in the Earth system could generate nonlinearities yielding 100 kyr cycles: Ashkenazy and Tziperman (2004) proposed a "seaice switch", Imbrie et al (2011) interpret the nonlinear terms of their models as a representation of ice-sheet instability, Ellis and Palmer (2016) consider a dust albedo feedback, and Omta et al (2016) invoke an instability of the carbonate cycle. There is a plethora of possible mechanisms, but the mathematical expression of these various mechanisms is scarcely firmly constrained.…”
Section: Introductionmentioning
confidence: 99%
“…Some mechanisms rely on a bifurcation occurring in the unforced climate system which fundamentally changes how the system operates (Ashwin and Ditlevsen, 2015;Ditlevsen, 2009;Huybers and Langmuir, 2017;Maasch and Salzman, 1990;Tziperman and Gildor, 2003). Other mechanisms invoke a "spontaneous" change, such as a shift between attractors due to subtle changes in insolation (Omta et al, 2015 Fig. 1 a) The LR04 stack of normalised isotopic oxygen anomalies in deep ocean sediment cores -a proxy for global ice volume and deep ocean temperatures (Lisiecki and Raymo, 2005).…”
mentioning
confidence: 99%